- Pengembangan Media Pembelajaran PowerPoint Interaktif Berbasis Kemampuan Berpikir Tingkat Tinggi (HOTS) Siswa Sekolah Dasar : - - Putri, Hanny Pramitha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an interactive PowerPoint learning media based on higher-order thinking skills for elementary school students, specifically on the topic of the effect of force on objects. The goal is to enhance students' higher-order thinking skills through the developed media. The research method used is Research and Development with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were 24 fourth-grade students of SD Islam Nurul Hidayah. Data collection techniques included observation, questionnaires, and test instruments. Product validity was assessed by media experts, content experts, classroom teachers, and student responses. The effectiveness of the media was evaluated by comparing the students’ pre-test and post-test results. The results showed: (1) the developed learning media was an interactive PowerPoint based on higher-order thinking skills, (2) validity tests yielded very feasible results, with media experts scoring 97%, content experts 82%, classroom teachers 81%, and student responses 90%, (3) the media’s effectiveness was demonstrated by the increase in average pre-test scores from 44 to 86 in the post-test. In conclusion, the interactive PowerPoint learning media based on higher-order thinking skills is feasible to use and effective in improving elementary students’ higher-order thinking abilities. Keywords: HOTS, Interactive PowerPoint learning media, R&D.